Interference with PPARγ in endothelium accelerates angiotensin II-induced endothelial dysfunction - Hu, Chunyan (Physiol Genomics, 2015)
The ligand activated nuclear receptor peroxisome proliferator-activated receptor γ (PPARγ) in the endothelium regulates vascular function and blood pressure (BP). We previously reported that transgenic mice (E-V290M) with selectively targeted endothelial-specific expression of dominant negative PPARγ exhibited endothelial dysfunction when treated with a high-fat diet, and exhibited an augmented pressor response to angiotensin II (ANG II). We hypothesize that interference with endothelial PPARγ would exacerbate ANG II-induced endothelial dysfunction. Endothelial function was examined in E-V290M mice infused with a subpressor dose of ANG II (120 ng·kg(−1)·min(−1)) or saline for 2 wk. ANG II infusion significantly impaired the responses to the endothelium-dependent agonist acetylcholine both in basilar and carotid arteries from E-V290M but not NT mice. This impairment was not due to increased BP, which was not significantly different in ANG II-infused E-V290M compared with NT mice. Superoxide levels, and expression of the pro-oxidant Nox2 gene was elevated, whereas expression of the anti-oxidant genes Catalase and SOD3 decreased in carotid arteries from ANG II-infused E-V290M mice. Increased p65 and decreased Iκ-Bα suggesting increased NF-κB activity was also observed in aorta from ANG II-infused E-V290M mice. The responses to acetylcholine were significantly improved both in basilar and carotid arteries after treatment with Tempol (1 mmol/l), a scavenger of superoxide. These findings provide evidence that interference with endothelial PPARγ accelerates ANG II-mediated endothelial dysfunction both in cerebral and conduit arteries through an oxidative stress-dependent mechanism, suggesting a role for endothelial PPARγ in protecting against ANG II-induced endothelial dysfunction.